Influence of vocal and aerodynamics aspects on the voice-related quality of life of older adults - SIQUEIRA, Larissa Thaís Donalonso (J Appl Oral Sci, 2020)
The pursuit for quality of life urged a better understanding of aspects involved in ageing to minimize its consequences. Although many studies investigated older adults’ voice, aspects affecting this population voice-related quality of life have not yet been explored. OBJECTIVE: To investigate how aerodynamics and vocal aspects are associated with voice-related quality of life in older adults. METHODOLOGY: fifty-six older adults aged 60 years or above – 39 women and 17 men – were evaluated. The following procedures were performed: application of the Voice-Related Quality of Life (V-RQOL) protocol; vocal assessment, including auditory-perceptual and acoustic analysis, from which we obtained fundamental frequency (F (0) ), standard deviation of fundamental frequency (SDF (0) ), shimmer, amplitude perturbation quotient (APQ), jitter, pitch period perturbation quotient (PPQ), and harmonics to noise ratio (HNR); aerodynamic assessment using a spirometer; and maximum phonation time (MPT) for /a/, /s/, /z/ and number counting. RESULTS: older adults tend to present high V-RQOL scores. Among women, roughness, APQ, and HNR parameters were negatively correlated with V-RQOL, whereas F (0) was positively. We found no correlation between spirometry measurements and V-RQOL. MPT for /a/, /z/, and number counting was positively correlated with V-RQOL solely among men. CONCLUSION: Vocal roughness and acoustic parameters have a negative impact on the quality of life of older women. Respiratory aspects related to the available air support for speaking affected the most the voice-related quality of life of older men.